Respuesta :

Answer:

[tex](g - f)(x) = log(x-3)- \sqrt[3]{12x +1} + 2[/tex]

Step-by-step explanation:

Given

[tex]f(x) = \sqrt[3]{12x +1} + 4[/tex]

[tex]g(x) = log(x-3)+6[/tex]

Required

Determine (g - f)(x)

In functions:

[tex](g - f)(x) = g(x) - f(x)[/tex]

So, we have:

[tex](g - f)(x) = log(x-3)+6 - (\sqrt[3]{12x +1} + 4)[/tex]

Open bracket

[tex](g - f)(x) = log(x-3)+6 - \sqrt[3]{12x +1} - 4[/tex]

Collect Like Terms

[tex](g - f)(x) = log(x-3)- \sqrt[3]{12x +1} - 4+6[/tex]

[tex](g - f)(x) = log(x-3)- \sqrt[3]{12x +1} + 2[/tex]

Answer:

[tex]→(g - f)(x) = g(x) - f(x) \\ → (log(x - 3) + 6) - (\sqrt[3]{12x + 1} + 4) \\→ log(x - 3) + 6 - \sqrt[3]{12x + 1} - 4 \\→\boxed{ log(x - 3) - \sqrt[3]{12x + 1} + 2}✓[/tex]

D. is the right answer.